Price Theory, Historically Considered: Smith, Ricardo, Marshall and Beyond - Bloch, Harry (History of Economics Thought Society, 2020)
Terminology is important. Price theory as the name given to the study of the determination of prices in markets reached ascendancy around the middle of the last century, having been little used at the start of the century and fading from use by the century’s end. Historically considering the theory of price determination from Smith to Ricardo, then to Marshall and beyond, not only reveals how changing terminology is related to the changing nature of the theory, but also identifies changes in the purposes the theory is attempting to achieve. Successive formulations embed different conceptions of what is being explained, which are reflected in the name given to the subject matter. The process is far from a straightforward exercise in improving the theory, with losses in what can be explained detracting from the purported gains in universality or precision.